The personalized application of biomaterials based on age and sexuality specific immune responses. (November 2021) - Xu, Jiaqi; Nie, Nanfang; Wu, Bingbing; Li, Yu; Gong, Lin; Yao, Xudong; Zou, Xiaohui; Ouyang, Hongwei
Abstract: Although biomaterials are widely utilized in clinics, it still follows the "one-fits-all" strategy. Biological variables such as age and sexuality have an impact on the host immune response and are not fully considered in the practice guidelines of the biomaterial implantation. In this study, we investigated the immuno-material interactions of six commonly used biomaterials (agarose, alginate, chitosan, CMC, GelMA and collagen type I) and constructed a population (with different ages and sexes) based transcriptome atlas. Protein and polysaccharide-based biomaterials elicited distinctive immune responses that protein-based materials preferred the NKT pathway to activate innate and adaptive immune response, whereas polysaccharide-based materials activated the cDCs to present antigen. The atlas further revealed the sex/age-related variabilities on the immune response followed by the polysaccharide treatment. As for sex bias, alginate and agarose stimulation significantly increased the proportion of naive CD4 + T cells in the female group, accompanied by the Th1 differentiation tendency, compared to the male group. Age-biased transcript showed alginate and chitosan would impair the extracellular matrix remodeling and up-regulate the apoptosis process in the elderly groups, compared to the young group. More attentions on the ingredient, age and sexuality effect of biomaterial implants should be paid during the clinical practice, especially for the polysaccharide-based materials. This experimental result is of great significance for the selection of biomaterials, particularly the blood contact materials, such as vessel or cardiac device, drug vehicles and hemostatic materials.